Juridical Review Of Sharing Joint Assets As Banking Credit Collateral: Analysis of Decision Number 1436/Pdt.G/2017/PA.Ckr - Nuri Hidayati; Widi Harsono (International Journal of Law and Society, 2024)
Joint assets are property acquired by a married couple, husband and wife can act on their joint assets with the consent of both parties. Marital Property Law has an important position in family life even when the marriage is still ongoing. In an activity regarding money loans at a bank, there is usually a handover of debt guarantees provided by the debtor to the creditor. In this case the debtors use joint assets as collateral for their credit agreement. The purpose of writing this thesis is to determine the legitimacy of using joint assets as collateral and the status of these joint assets by analyzing various sources of applicable law in Indonesia. In this analysis, it was found that joint assets used as collateral for credit cannot be processed in terms of assets back and forth until the obligation debt of debtors is completed.